Religious Renewal in France, 1789-1870 The Roman Catholic Church between Catastrophe and Triumph - Price, Roger (Springer International Publishing, 2018)
This book provides a study of the manner in which the Roman Catholic Church in France responded to successive revolutions between 1789 and 1870 as well as to the cultural upheaval associated with accelerating socio-economic change. It focuses on the Church as an institution engaged in a dynamic process of (re)Christianization and determined, as the only repository of the true faith of Jesus Christ, to fortify belief , and to combat the 'Satanic' forces of moral corruption and revolutionary chaos and create a 'counter society', the société parfaite. Discussion of the Church as an institution in crisis, of the recruitment, instruction and mind-sets of its bishops, parish clergy, and the members of religious orders, of its hierarchical structures and internal discipline, and of the need to compensate for the losses suffered during a period of revolutionary upheaval, provides the basis for an exploration of its evolving doctrine(s) and sense of purpose; for an assessment of the pastoral care provided to parish communities; and of the leadership and moral qualities of the clergy; before final consideration of the reception of the religious message(s).